Composite hydroxyapatite microspheres, method for preparing the same and use thereof
Patent Information
- Application Number
- CN202611234699.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-08-14
AI Technical Summary
[0002]交联透明质酸(HA)是目前临床用量最大的医美填充材料,其具有良好的组织贴合性与代谢安全性,但纯交联HA力学支撑强度弱且在体内易降解,无法满足长效轮廓塑形需求
[0028]工艺简单:全部水溶性物料、交联剂、pH调节剂均在水相预混完毕,油相及乳液阶段无需补料以及调节PH,解决传统方式的操作复杂性以及批次重复性等问题。
Smart Images

Figure CN122768513B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical polymer soft tissue filling materials, specifically to composite hydroxyapatite microspheres, their preparation methods, and applications. Background Technology
[0002] Cross-linked hyaluronic acid (HA) is currently the most widely used cosmetic filler material in clinical practice. It has good tissue conformation and metabolic safety. However, pure cross-linked HA has weak mechanical support and is easily degraded in vivo, which cannot meet the needs of long-term contouring. Current technology usually combines it with hydroxyapatite (HAP) to improve the rigidity and support of the material. However, the mainstream preparation method is to first prepare HAP powder and then physically blend it with HA gel. The HA and HAP prepared in this way are only physically embedded, without molecular-level interfacial bonding. When body fluids seep into the interface between the two phases, it is easy to cause interfacial delamination and rapid decay of mechanical modulus. Summary of the Invention
[0003] In view of this, the technical problem to be solved by the present invention is to provide composite hydroxyapatite microspheres, their preparation method and application. The composite hydroxyapatite microspheres provided by the present invention are hydroxy amino acid in-situ bridging hyaluronic acid-composite hydroxyapatite microspheres based on a one-step fully premixed aqueous emulsification process. They have the advantages of softness and adaptability, rigid support, long-term structural stability and excellent biocompatibility. They have high applicability in subcutaneous medical aesthetic filling scenarios such as local depressions in the human face and fine adjustment of facial contours. The manufacturing process is simple and the cost is low.
[0004] This invention provides a method for preparing composite hydroxyapatite microspheres, comprising the following steps: adding an aqueous phase containing hyaluronic acid (HA), 1,4-butanediol diglycidyl ether (BDDE), hydroxy amino acids, calcium source, and phosphorus source at pH 10-11 to an oil phase containing an emulsifier for isothermal emulsification and molding, and then heating to carry out a cross-linking mineralization reaction to obtain composite hydroxyapatite microspheres.
[0005] The hydroxy amino acids used in this invention are selected from one or more of L-serine, L-threonine, and L-tyrosine. This invention utilizes the intermolecular hydrogen bonds between the hydroxy amino acids and amino acids (HA). The carboxyl and hydroxyl groups of the HA molecular chain form a high-density hydrogen bond network with the hydroxyl and amino groups of the hydroxy amino acids, achieving uniform anchoring of amino acid monomers (AA) in the inter-chain spaces of the HA chain. Subsequently, calcium and phosphate ions in the aqueous phase are chelated and anchored by the amino acids. After emulsification, hydroxyapatite (HAP) crystals are grown in situ inside the microdroplets. One end of the amino acid is bonded to the HA organic network, and the other end is coordinated with the HAP inorganic crystal, forming a three-in-one in-situ interfacial bridging structure of HA-AA-HAP.
[0006] The method for preparing composite hydroxyapatite microspheres provided by this invention involves first adding an aqueous phase containing hyaluronic acid, 1,4-butanediol diglycidyl ether, hydroxy amino acids, a calcium source, and a phosphorus source (pH 10-11) to an oil phase containing an emulsifier for isothermal emulsification and molding. Preferably, the volume ratio of the oil phase to the aqueous phase is 1:(0.45-0.55).
[0007] The aqueous phase of this invention is obtained by mixing hyaluronic acid, 1,4-butanediol diglycidyl ether, hydroxy amino acids, a calcium source, and a phosphorus source in water, and controlling the pH of the system to be 10-11. The hyaluronic acid used in this invention is preferably medical-grade hyaluronic acid. The molecular weight of the hyaluronic acid used in this invention is preferably 800 kDa-1500 kDa. The mass-volume content of the hyaluronic acid and water in the aqueous phase is 1%-3%; the added mass of 1,4-butanediol diglycidyl ether is 1%-5% of the mass of the hyaluronic acid; the added mass of the hydroxy amino acids is 5%-15% of the mass of the hyaluronic acid; the calcium-phosphorus molar ratio of the calcium source and phosphorus source is 1.6-1.7, preferably 1.65-1.7, more preferably 1.67; the mass-volume content of the calcium source in the water in the aqueous phase is 0.9%-1.0%; and the mass-volume content of the phosphorus source in the water in the aqueous phase is 0.3%-0.4%. The calcium and phosphorus sources described in this invention are both water-soluble substances. The calcium source is preferably selected from one or more of calcium nitrate, calcium chloride, and calcium sulfate, more preferably from calcium nitrate. The phosphorus source is preferably selected from one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and sodium dihydrogen phosphate, more preferably from diammonium hydrogen phosphate. The pH of the system described in this invention is preferably controlled using ammonia water. The 1,4-butanediol diglycidyl ether described in this invention functions as a crosslinking agent.
[0008] In some embodiments of the present invention, hyaluronic acid is added to water and stirred for 30 to 60 minutes at 25°C to 30°C and 300 to 500 r / min to fully hydrate and dissolve the hyaluronic acid, resulting in a homogeneous aqueous solution of hyaluronic acid. 1,4-Butanediol diglycidyl ether is added to the aqueous solution of hyaluronic acid and stirring is continued for 15 to 20 minutes to uniformly disperse the 1,4-butanediol diglycidyl ether in the aqueous solution of hyaluronic acid. Subsequently, hydroxy amino acids are added and stirred for 20 to 30 minutes to fully dissolve and disperse the hydroxy amino acids. Then, a calcium source and a phosphorus source are added sequentially and stirred for 15 to 20 minutes to uniformly disperse the calcium source and phosphorus source in the system. After all components are mixed evenly, the pH of the system is adjusted to 10 to 11 and stirring is continued for 10 to 15 minutes to maintain a uniform and stable pH, resulting in the aqueous phase.
[0009] In other embodiments of the present invention, hyaluronic acid and water are stirred and dissolved at 25°C to 30°C and 300 r / min to 500 r / min for 30 min to 60 min to obtain an aqueous solution of hyaluronic acid. To ensure complete dissolution of the hyaluronic acid, 1,4-butanediol diglycidyl ether is added, and the pH of the system is adjusted to 10 to 11. Hydroxy amino acids are then added to the system, and stirring continues for 20 min to 30 min until the hydroxy amino acids are completely dissolved. At this point, the hydroxyl groups on the side chains of the amino acids form hydrogen bonds with the hydroxyl and carboxyl groups of the HA molecular chains, achieving initial binding between the amino acids and HA, resulting in a uniform and transparent system. Calcium and phosphorus sources are then added to the system, and stirring continues for 15 min to 20 min until the calcium and phosphorus sources are completely dissolved. At this point, the hydroxyl and amino groups of the amino acids chelate with calcium and phosphate ions, achieving site-specific anchoring of calcium and phosphorus ions. The system remains uniform without significant precipitation, yielding the aqueous phase.
[0010] The oil phase of this invention is obtained by mixing an emulsifier and an oil phase solvent. Specifically, the emulsifier and the oil phase solvent are mixed at 25°C~30°C and 500 r / min~700 r / min for 10 min~15 min to completely dissolve the emulsifier in the oil phase solvent, resulting in an oil phase containing the emulsifier. Preferably, the oil phase containing the emulsifier of this invention is obtained by mixing Tween 60 and medical-grade liquid paraffin; using Tween 60 as the emulsifier results in uniform dispersion of the aqueous droplets, higher sphericity of the microspheres, and less tendency for adhesion. In some embodiments of this invention, a certain amount of medical-grade liquid paraffin is taken, and Tween 60 is added as an emulsifier. The mixture is stirred at 25°C~30°C and a stirring speed of 500-700 r / min for 10 min~15 min to completely dissolve the Tween 60 in the medical-grade liquid paraffin, resulting in a uniform oil phase containing the emulsifier.
[0011] This invention involves adding an aqueous phase containing hyaluronic acid, 1,4-butanediol diglycidyl ether, hydroxy amino acids, a calcium source, and a phosphorus source (pH 10-11) to an oil phase containing an emulsifier for isothermal emulsification. Specifically, the aqueous phase is slowly added dropwise to the oil phase while stirring and isothermal emulsification is performed to form uniformly dispersed initial microspheres. The temperature is maintained stable during emulsification to avoid uneven emulsification leading to differences in microsphere size. Preferably, the isothermal emulsification temperature is 25°C-30°C, and the isothermal emulsification time is 20-30 minutes. The isothermal emulsification is performed with stirring at a speed of 400-700 r / min, preferably 500-700 r / min, and more preferably 500-650 r / min.
[0012] After isothermal emulsification and molding, the present invention further heats up to carry out a cross-linking mineralization reaction to obtain composite hydroxyapatite microspheres. The temperature of the cross-linking mineralization reaction is 35℃~45℃, preferably 38℃~42℃; the reaction time is 2 h~4 h, preferably 2.5 h~3.5 h. Preferably, the cross-linking mineralization reaction is carried out under stirring at a speed of 250 r / min~400 r / min, more preferably 300 r / min. During the cross-linking mineralization reaction, three reactions occur simultaneously: ① BDDE cross-links with HA molecular chains to form a stable three-dimensional network framework; ② Under the induction of amino acids, calcium and phosphorus ions slowly nucleate and grow in situ into HAP inside the initial microspheres; ③ Amino acids further form a strong interfacial bond with the HA cross-linking framework and HAP, realizing molecular-level composite of organic and inorganic phases, ultimately forming composite hydroxyapatite microspheres.
[0013] Preferably, after the cross-linking mineralization reaction, the present invention further includes separating, washing, and solidifying the reaction system to obtain composite hydroxyapatite microspheres. Specifically, after the cross-linking mineralization reaction, the reacted material is separated by precipitation, and then the precipitated material is washed alternately with ethanol and water. The washed material is then solidified in a phosphate buffer solution with a pH of 7.2-7.6 at 35-40°C for 40-56 hours, and then transferred to 0-5°C for further solidification for 64-80 hours to obtain composite hydroxyapatite microspheres.
[0014] The present invention provides a method for preparing composite hydroxyapatite microspheres, which is an in-situ hyaluronic acid-composite hydroxyapatite microsphere preparation method using an all-component premixed aqueous emulsification process. Hyaluronic acid, 1,4-butanediol diglycidyl ether, hydroxy amino acids, calcium source, and phosphorus source are pre-uniformly dispersed in the same aqueous system. An oil phase is prepared using liquid paraffin as the continuous phase and Tween 60 as the emulsifier. The obtained premixed aqueous phase is dispersed in the oil phase to form emulsion droplets. Hyaluronic acid crosslinking and in-situ mineralization of hydroxyapatite occur inside the emulsion droplets, allowing hydroxy amino acids to participate in the interfacial composite between hyaluronic acid and hydroxyapatite. The hyaluronic acid crosslinking, hyaluronic acid-amino acid adsorption, and amino acid-mediated in-situ calcium and phosphorus mineralization steps are completed simultaneously, thereby obtaining composite hydroxyapatite microspheres with a relatively stable combination of organic and inorganic phases. The process is simple, requires no stepwise reactions, is easy to operate, and has low mass production cost.
[0015] The present invention also provides composite hydroxyapatite microspheres, comprising:
[0016] A cross-linked network of 1,4-butanediol diglycidyl ether and hyaluronic acid;
[0017] Hydroxy amino acids bonded to the cross-linked network;
[0018] Hydroxyapatite grown in situ on the hydroxy amino acids;
[0019] The hydroxy amino acid is selected from one or more of L-serine, L-threonine, and L-tyrosine.
[0020] The composite hydroxyapatite microspheres provided by this invention can be obtained by the aforementioned preparation method. The composite hydroxyapatite microspheres provided by this invention are amino acid-induced organic-inorganic composite hydroxyapatite microspheres; their physical morphology is a white powder; and their particle size is 20 μm to 60 μm.
[0021] The composite hydroxyapatite microspheres provided by this invention form a three-in-one interfacial bridging structure of hyaluronic acid, hydroxy amino acids, and calcium hydroxyphosphate. Utilizing the in-situ interfacial bridging effect of hydrogen bonds in hydroxy amino acids, it combines softness and adaptability, rigid support, long-term structural stability, and excellent biocompatibility, overcoming the shortcomings of existing hyaluronic acid-composite hydroxyapatite microsphere products, such as weak organic-inorganic interfacial bonding and easy disintegration and failure of particles under long-term body fluid conditions. Specifically, the initial storage modulus of the composite hydroxyapatite microspheres of this invention is 900 Pa~1050 Pa, and the initial loss modulus is ≤75 Pa; after soaking in PBS at 37℃ and pH=7.4 for 6 months, the storage modulus retention rate is ≥90%.
[0022] The present invention also provides a subcutaneous cosmetic filler material, including composite hydroxyapatite microspheres obtained by any of the preparation methods described above or any of the composite hydroxyapatite microspheres described above.
[0023] The subcutaneous cosmetic filler material of the present invention can be obtained from the above-mentioned composite hydroxyapatite microspheres; specifically, it is obtained by suspending the above-mentioned composite hydroxyapatite microspheres in physiological saline or PBS.
[0024] The subcutaneous cosmetic filler material of the present invention can also be obtained by physically mixing the above-mentioned composite hydroxyapatite microspheres and a medically acceptable carrier; in this case, the subcutaneous cosmetic filler material includes the above-mentioned composite hydroxyapatite microspheres and a medically acceptable carrier. Preferably, the medically acceptable carrier includes one or more of cross-linked hyaluronic acid and sodium carboxymethyl cellulose.
[0025] The subcutaneous cosmetic filler material of the present invention may further include the above-mentioned composite hydroxyapatite microspheres and a medically acceptable carrier coated on the composite hydroxyapatite microspheres; preferably, the medically acceptable carrier includes one or more of cross-linked hyaluronic acid and sodium carboxymethyl cellulose. In some embodiments of the present invention, the above-mentioned composite hydroxyapatite microspheres and the medically acceptable carrier aqueous solution are mixed and stirred at a high speed of 1000 r / min to 2000 r / min, and then reacted under the action of a cross-linking agent to form a shell composed of the medically acceptable carrier on the composite hydroxyapatite microspheres, thereby obtaining the subcutaneous cosmetic filler material comprising the above-mentioned composite hydroxyapatite microspheres and the medically acceptable carrier coated on the composite hydroxyapatite microspheres.
[0026] This invention provides composite hydroxyapatite microspheres, their preparation method, and applications. Addressing the pain points of existing hyaluronic acid-composite hydroxyapatite filler particles, which employ a step-by-step preparation process, resulting in particle agglomeration, easy separation of organic and inorganic phases, and high production costs in medical aesthetic applications, this invention provides microspheres based on a one-step fully premixed aqueous emulsification process, in-situ bridging hyaluronic acid-composite hydroxyapatite with hydroxy amino acids. These microspheres possess softness and adaptability, rigid support, long-term structural stability, and excellent biocompatibility, making them highly applicable to subcutaneous medical aesthetic filling scenarios such as localized facial depressions and facial contour adjustments. The manufacturing process is simple and low-cost.
[0027] Compared with the prior art, the composite hydroxyapatite microspheres provided by the present invention have at least the following beneficial effects:
[0028] The process is simple: all water-soluble materials, crosslinking agents, and pH adjusters are premixed in the aqueous phase. No additional materials or pH adjustment are required in the oil phase and emulsion stages, which solves the problems of operational complexity and batch repeatability in traditional methods.
[0029] Mechanical compatibility advantages: The initial storage modulus G' of the finished microspheres is 900 Pa~1050 Pa, and the loss modulus G''≤75 Pa. The high storage modulus provides subcutaneous anti-compression rigid support, and the low loss modulus ensures that the microspheres can conform to the deformation of soft tissue and eliminate the hard foreign body feeling after injection.
[0030] Long-term size stability: After soaking in PBS at 37℃ for 6 months, the modulus residual rate is ≥90%, indicating that the microspheres have long-term stability.
[0031] Biocompatibility: All raw materials are endogenous substances in the human body or medical excipients listed in the pharmacopoeia. HA and HAP are clinically mature filler materials, and hydroxy amino acids can be metabolized endogenously in the human body. The microspheres degrade slowly without the precipitation of free particles. Based on common knowledge, it can be determined that they have excellent biocompatibility and avoid the risks of subcutaneous granulomas and chronic inflammation. Attached Figure Description
[0032] Figure 1 The image below shows the organic-inorganic composite hydroxyapatite microspheres prepared in Example 1 under a microscope.
[0033] Figure 2 The rheological properties characterization diagram of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 1 is shown below.
[0034] Figure 3 Figure 1 shows the stability study of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 1 after 1 month.
[0035] Figure 4 Figure 1 shows the 3-month stability study of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 1.
[0036] Figure 5 Figure 1 shows the 6-month stability study of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 1.
[0037] Figure 6 The image below shows the organic-inorganic composite hydroxyapatite microspheres prepared in Example 2;
[0038] Figure 7 The rheological properties characterization diagram of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 2 is shown below.
[0039] Figure 8 Figure 1 shows the stability study of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 2 after 1 month.
[0040] Figure 9 Figure 1 shows the 3-month stability study of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 2.
[0041] Figure 10 Figure 6 shows the stability study of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 2 after 6 months;
[0042] Figure 11 The image below shows the organic-inorganic composite hydroxyapatite microspheres prepared in Example 3;
[0043] Figure 12 The rheological properties characterization diagram of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 3 is shown below.
[0044] Figure 13 Figure 1 shows the stability study of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 3 after 1 month.
[0045] Figure 14 Figure 3 shows the stability study of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 3 after 3 months.
[0046] Figure 15 Figure 6 shows the stability study of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 3 after 6 months.
[0047] Figure 16 The image below shows the product prepared for Comparative Example 1 under a microscope.
[0048] Figure 17 Rheological property characterization diagram of the product prepared for Comparative Example 1;
[0049] Figure 18 The image below shows a microscope image of the product prepared for Comparative Example 2.
[0050] Figure 19 Rheological property characterization diagram of the product prepared for Comparative Example 2;
[0051] Figure 20 The image below shows a microscope image of the product prepared for Comparative Example 3.
[0052] Figure 21 Rheological property characterization diagram of the product prepared in Comparative Example 3;
[0053] Figure 22 The image below shows a microscope image of fully swollen, cross-linked hyaluronic acid-encapsulated organic-inorganic composite hydroxyapatite microspheres prepared in Application Example 1. Detailed Implementation
[0054] This invention discloses composite hydroxyapatite microspheres, their preparation method, and applications. Those skilled in the art can refer to this document and appropriately modify the process parameters to achieve the desired results. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments, and those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0055] The present invention will be further described below with reference to the embodiments:
[0056] Example 1
[0057] 1. Preparation of the aqueous phase: At room temperature (28℃), 10.0 g of hyaluronic acid (1000 kDa) was slowly added to 500 mL of deionized water, and stirred at 400 r / min for 45 min to fully hydrate and dissolve the hyaluronic acid, forming a homogeneous, gel-free aqueous solution. 0.3 g of BDDE crosslinking agent was then directly added to the above hyaluronic acid aqueous solution, and stirring was continued for 15 min to ensure that BDDE was fully dispersed in the hyaluronic acid aqueous solution, achieving homogeneous distribution of the crosslinking agent throughout the aqueous system and pre-constructing the crosslinking reaction system. 1.0 g of L-serine was then added to the system, and stirring was continued for 25 min to ensure complete dissolution and dispersion of the serine, completing the pre-bonding and fixation of the amino acid with the organic framework. Subsequently, 4.7 g of calcium nitrate tetrahydrate and 1.58 g of diammonium hydrogen phosphate were added sequentially, and stirring was continued for 20 min to ensure that calcium and phosphorus ions were uniformly dispersed in the system. The hydroxyl and amino groups of serine chelated and anchored the free calcium and phosphorus ions at specific sites, forming a stable mineralization precursor. After all materials have been added and stirred evenly, ammonia solution is slowly added dropwise to the aqueous system to adjust the pH to 11, and the system is stirred continuously for 10 minutes until the overall pH of the system is uniform and stable, so as to promote the subsequent cross-linking reaction.
[0058] 2. Preparation of the oil phase: Take 950 mL of medical liquid paraffin as the continuous oil phase, add 50.0 g of Tween 60 emulsifier, and stir at 28℃ and 600 r / min for 15 min to completely dissolve and disperse Tween 60, so as to obtain a clear, homogeneous and stable oil phase system for later use.
[0059] 3. Emulsification and molding of the aqueous phase with the oil phase: Maintaining the oil phase system temperature at 28℃ and the stirring speed at 600 r / min, the premixed aqueous phase prepared above is slowly and uniformly added dropwise to the oil phase system. After the addition is complete, continue emulsification at a constant temperature for 25 min. Relying on the interfacial tension between oil and water and the mechanical shearing action, the homogeneous aqueous solution is dispersed into micron-sized independent spherical droplets, forming a stable emulsion system.
[0060] 4. Constant-temperature continuous reaction to complete cross-linking, solidification, and in-situ mineralization: After emulsification stabilization, the system is heated to 40℃, the stirring speed is adjusted to 400 r / min, and the reaction is continued at a constant temperature for 3 h. BDDE, which is pre-uniformly dispersed in aqueous droplets, undergoes a cross-linking reaction with hyaluronic acid molecular chains, gradually solidifying to form a stable three-dimensional network framework, rapidly locking the spherical structure of microspheres. Calcium phosphate ions, anchored by serine functional groups, nucleate and grow in situ and orderly within the HA cross-linking network under the directional induction of serine hydroxyl groups, generating uniformly sized calcium hydroxyphosphate nanocrystals. Moreover, serine continues to play an organic-inorganic interface bridging role, firmly binding the HA organic network and the calcium hydroxyphosphate inorganic crystals, achieving molecular-level composite and completely solving the technical defect of two-phase stratification.
[0061] 5. Separation, washing, and curing to obtain the finished microspheres: After the reaction, the microspheres were allowed to cool naturally to room temperature and stand for 30 minutes to precipitate. The precipitate was then collected. The microspheres were washed twice with anhydrous ethanol to completely remove residual liquid paraffin and Tween 60 from the surface. They were then washed four times with deionized water to remove unreacted small molecule raw materials and free ions. The obtained microspheres were placed in a phosphate buffer solution with a pH of 7.4 and cured at 37°C for 48 hours. They were then transferred to a 4°C environment and cured for another 72 hours to obtain organic-inorganic composite hydroxyapatite microspheres with uniform particle size.
[0062] To further verify the support and stability of the prepared microspheres, the rheological properties and long-term stability of the microspheres were determined using an Anton Paar rotating plate rheometer. Testing equipment: rotating plate rheometer; test probe: 25 mm parallel plates, plate spacing 1 mm; testing environment: 25℃; testing mode: small-amplitude oscillation frequency scanning; oscillation frequency fixed at 1 Hz, strain value 0.5%, the storage modulus was measured to be 990 Pa, and the loss modulus to be 30 Pa. Long-term stability samples: The microsphere suspension was immersed in sterile PBS buffer (pH=7.4) at 37℃ in the dark. The microspheres were removed after 1 month, 3 months, and 6 months, and the rheological parameters were directly remeasured.
[0063] Test results: After 1 month, its storage modulus was 950 Pa; after 3 months, its storage modulus was 930 Pa; and after 6 months, its storage modulus was 900 Pa. After 6 months of aging by soaking in PBS body fluid, the storage modulus residual rate of the microspheres of this invention reached more than 90%, indicating that it has good stability.
[0064] like Figure 1 As shown, Figure 1 The image below shows a microscopic view of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 1. Figure 2 As shown, Figure 2 The rheological properties characterization diagram is shown for the organic-inorganic composite hydroxyapatite microspheres prepared in Example 1. Figures 3-5 As shown, Figure 3 , Figure 4 , Figure 5 The figures show the stability of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 1 after 1 month, 3 months, and 6 months, respectively.
[0065] Example 2
[0066] 1. Preparation of the aqueous phase: At room temperature (28℃), 10.0 g of hyaluronic acid (1000 kDa) was slowly added to 500 mL of deionized water, and stirred at 400 r / min for 45 min to fully hydrate and dissolve the hyaluronic acid, forming a homogeneous, gel-free aqueous solution. 0.3 g of BDDE crosslinking agent was then added directly to the above hyaluronic acid aqueous solution, and stirring was continued for 15 min to ensure that BDDE was fully dispersed in the hyaluronic acid aqueous solution, achieving homogeneous distribution of the crosslinking agent throughout the aqueous system and pre-constructing the crosslinking reaction system. 1.0 g of L-threonine was then added to the system, and stirring was continued for 25 min to completely dissolve and disperse the threonine, completing the pre-bonding and fixation of the amino acid with the organic framework. Subsequently, 4.7 g of calcium nitrate tetrahydrate and 1.58 g of diammonium hydrogen phosphate were added sequentially, and stirring was continued for 20 min to ensure that calcium and phosphorus ions were uniformly dispersed in the system. The hydroxyl and amino groups of threonine chelated and anchored the free calcium and phosphorus ions at specific sites, forming a stable mineralization precursor. After all materials have been added and stirred evenly, ammonia solution is slowly added dropwise to the aqueous system to adjust the pH to 11, and the system is stirred continuously for 10 minutes until the overall pH of the system is uniform and stable, so as to promote the subsequent cross-linking reaction.
[0067] 2. Preparation of the oil phase: Take 950 mL of medical liquid paraffin as the continuous oil phase, add 50.0 g of Tween 60 emulsifier, and stir at 28℃ and 600 r / min for 15 min to completely dissolve and disperse Tween 60, so as to obtain a clear, homogeneous and stable oil phase system for later use.
[0068] 3. Emulsification and molding of the aqueous phase with the oil phase: Maintaining the oil phase system temperature at 28℃ and the stirring speed at 600 r / min, the premixed aqueous phase prepared above is slowly and uniformly added dropwise to the oil phase system. After the addition is complete, continue emulsification at a constant temperature for 25 min. Relying on the interfacial tension between oil and water and the mechanical shearing action, the homogeneous aqueous solution is dispersed into micron-sized independent spherical droplets, forming a stable emulsion system.
[0069] 4. Constant-temperature continuous reaction to complete cross-linking, solidification, and in-situ mineralization: After emulsification and stabilization, the system is heated to 40℃, the stirring speed is adjusted to 400 r / min, and the reaction is continued at a constant temperature for 3 h. BDDE, which is pre-uniformly dispersed in aqueous droplets, undergoes a cross-linking reaction with hyaluronic acid molecular chains, gradually solidifying to form a stable three-dimensional network framework, rapidly locking the spherical structure of microspheres. Calcium phosphate ions, anchored by threonine functional groups, nucleate and grow in situ and orderly within the HA cross-linking network under the directional induction of threonine hydroxyl groups, generating uniformly sized calcium hydroxyphosphate nanocrystals. Moreover, threonine continues to play a bridging role at the organic-inorganic interface, firmly binding the HA organic network and the calcium hydroxyphosphate inorganic crystals, achieving molecular-level composite and completely solving the technical defect of two-phase stratification.
[0070] 5. Separation, washing, and curing to obtain the finished microspheres: After the reaction, the microspheres were allowed to cool naturally to room temperature and stand for 30 minutes to precipitate. The precipitate was then collected. The microspheres were washed twice with anhydrous ethanol to completely remove residual liquid paraffin and Tween 60 from the surface. They were then washed four times with deionized water to remove unreacted small molecule raw materials and free ions. The obtained microspheres were placed in a phosphate buffer solution at pH 7.4 and cured at 37°C for 48 hours. They were then transferred to a 4°C environment and cured for another 72 hours to obtain uniformly sized organic-inorganic composite calcium hydroxyphosphate microspheres.
[0071] The rheological properties and stability of the microspheres were determined in the same manner as in Example 1. Their rheological properties were: storage modulus 930 Pa, loss modulus 28 Pa. The storage modulus after 1 month was 890 Pa, after 3 months it was 850 Pa, and after 6 months it was 838 Pa.
[0072] like Figure 6 As shown, Figure 6 The image below shows a microscopic view of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 2. Figure 7 As shown, Figure 7 The rheological properties characterization diagram is shown for the organic-inorganic composite hydroxyapatite microspheres prepared in Example 2. Figures 8-10 As shown, Figure 8 , Figure 9 , Figure 10 The figures show the stability of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 2 after 1 month, 3 months, and 6 months, respectively.
[0073] Example 3
[0074] 1. Preparation of the aqueous phase: At room temperature (28℃), 10.0 g of hyaluronic acid (1000 kDa) was slowly added to 500 mL of deionized water, and stirred at 400 r / min for 45 min to fully hydrate and dissolve the hyaluronic acid, forming a homogeneous, gel-free aqueous solution. 0.3 g of BDDE crosslinking agent was then directly added to the above hyaluronic acid aqueous solution, and stirring was continued for 15 min to ensure that BDDE was fully dispersed in the hyaluronic acid aqueous solution, achieving homogeneous distribution of the crosslinking agent throughout the aqueous system and pre-constructing the crosslinking reaction system. 1.0 g of L-tyrosine was then added to the system, and stirring was continued for 25 min to ensure complete dissolution and dispersion of the tyrosine, completing the pre-bonding and fixation of the amino acid with the organic framework. Subsequently, 4.7 g of calcium nitrate tetrahydrate and 1.58 g of diammonium hydrogen phosphate were added sequentially, and stirring was continued for 20 min to ensure that calcium and phosphorus ions were uniformly dispersed in the system. The hydroxyl and amino groups of tyrosine chelated and anchored the free calcium and phosphorus ions at specific sites, forming a stable mineralization precursor. After all materials have been added and stirred evenly, ammonia solution is slowly added dropwise to the aqueous system to adjust the pH to 11, and the system is stirred continuously for 10 minutes until the overall pH of the system is uniform and stable, so as to promote the subsequent cross-linking reaction.
[0075] 2. Preparation of the oil phase: Take 950 mL of medical liquid paraffin as the continuous oil phase, add 50.0 g of Tween 60 emulsifier, and stir at 28℃ and 600 r / min for 15 min to completely dissolve and disperse Tween 60, so as to obtain a clear, homogeneous and stable oil phase system for later use.
[0076] 3. Emulsification and molding of the aqueous phase with the oil phase: Maintaining the oil phase system temperature at 28℃ and the stirring speed at 600 r / min, the premixed aqueous phase prepared above is slowly and uniformly added dropwise to the oil phase system. After the addition is complete, continue emulsification at a constant temperature for 25 min. Relying on the interfacial tension between oil and water and the mechanical shearing action, the homogeneous aqueous solution is dispersed into micron-sized independent spherical droplets, forming a stable emulsion system.
[0077] 4. Constant-temperature continuous reaction to complete cross-linking, solidification, and in-situ mineralization: After emulsification and stabilization, the system is heated to 40℃, the stirring speed is adjusted to 400 r / min, and the reaction is continued at a constant temperature for 3 h. BDDE, which is pre-uniformly dispersed in aqueous droplets, undergoes a cross-linking reaction with hyaluronic acid molecular chains, gradually solidifying to form a stable three-dimensional network framework, rapidly locking the spherical structure of microspheres. Calcium phosphate ions, anchored by tyrosine functional groups, nucleate and grow in situ and orderly within the HA cross-linking network under the directional induction of tyrosine hydroxyl groups, generating uniformly sized calcium hydroxyphosphate nanocrystals. Moreover, tyrosine continues to play a bridging role at the organic-inorganic interface, firmly binding the HA organic network and the calcium hydroxyphosphate inorganic crystals, achieving molecular-level composite and completely solving the technical defect of two-phase stratification.
[0078] 5. Separation, washing, and curing to obtain the finished microspheres: After the reaction, the microspheres were allowed to cool naturally to room temperature and stand for 30 minutes to precipitate. The precipitate was then collected. The microspheres were washed twice with anhydrous ethanol to completely remove residual liquid paraffin and Tween 60 from the surface. They were then washed four times with deionized water to remove unreacted small molecule raw materials and free ions. The obtained microspheres were placed in a phosphate buffer solution at pH 7.4 and cured at 37°C for 48 hours. They were then transferred to a 4°C environment and cured for another 72 hours to obtain uniformly sized organic-inorganic composite calcium hydroxyphosphate microspheres.
[0079] The rheological properties and stability of the microspheres were determined in the same manner as in Example 1. Their rheological properties were: storage modulus 920 Pa, loss modulus 35 Pa. The storage modulus after 1 month was 900 Pa, after 3 months it was 890 Pa, and after 6 months it was 840 Pa.
[0080] like Figure 11 As shown, Figure 11 The image below shows a microscopic view of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 3. Figure 12 As shown, Figure 12 The rheological properties characterization diagram is shown for the organic-inorganic composite hydroxyapatite microspheres prepared in Example 3. Figures 13-15 As shown, Figure 13 , Figure 14 , Figure 15 The figures show the stability of the organic-inorganic composite hydroxyapatite microspheres prepared in Example 3 after 1 month, 3 months, and 6 months, respectively.
[0081] Comparative Example 1
[0082] 1. Preparation of the aqueous phase: At room temperature (28℃), 10.0 g of hyaluronic acid (1000 kDa) was slowly added to 500 mL of deionized water, and stirred at 400 r / min for 45 min to fully hydrate and dissolve the hyaluronic acid, forming a homogeneous, gel-free aqueous solution. 0.3 g of BDDE crosslinking agent was then directly added to the above hyaluronic acid aqueous solution, and stirred continuously for 15 min to ensure that BDDE was fully dispersed in the hyaluronic acid aqueous solution, achieving uniform distribution of the crosslinking agent in the aqueous system and pre-constructing the crosslinking reaction system. Subsequently, 4.7 g of calcium nitrate tetrahydrate and 1.58 g of diammonium hydrogen phosphate were added sequentially, and stirred continuously for 20 min to ensure uniform dispersion of calcium and phosphate ions in the system. After all materials were added and stirred evenly, ammonia solution was slowly added dropwise to the aqueous system to adjust the pH to 11, and stirred continuously for 10 min until the overall pH of the system was uniform and stable to promote the subsequent crosslinking reaction.
[0083] 2. Preparation of the oil phase: Take 950 mL of medical liquid paraffin as the continuous oil phase, add 50.0 g of Tween 60 emulsifier, and stir at 28℃ and 600 r / min for 15 min to completely dissolve and disperse Tween 60, so as to obtain a clear, homogeneous and stable oil phase system for later use.
[0084] 3. Emulsification and molding of the aqueous phase with the oil phase: Maintaining the oil phase system temperature at 28℃ and the stirring speed at 600 r / min, the premixed aqueous phase prepared above is slowly and uniformly added dropwise to the oil phase system. After the addition is complete, continue emulsification at a constant temperature for 25 min. Relying on the interfacial tension between oil and water and the mechanical shearing action, the homogeneous aqueous solution is dispersed into micron-sized independent spherical droplets, forming a stable emulsion system.
[0085] 4. Constant temperature and continuous reaction to complete cross-linking and curing: After emulsification and stabilization, heat the system to 40℃, adjust the stirring speed to 400 r / min, and continue the reaction at a constant temperature for 3 h.
[0086] 5. Separation, washing, and solidification to obtain the finished product: After the reaction is complete, allow the mixture to cool naturally to room temperature and let it stand for 30 minutes to precipitate. Collect the microsphere precipitate. Wash twice with anhydrous ethanol to completely remove residual liquid paraffin and Tween 60 from the surface; then wash four times with deionized water to remove unreacted small molecule raw materials and free ions. After solidification, the product is obtained.
[0087] Unlike the well-defined, uniformly sized, and well-dispersed organic-inorganic composite microspheres obtained in Example 1, the product in this comparative example exhibits significant defects, as detailed below:
[0088] Unable to form a regular microsphere structure: Because the system does not contain hydroxyl amino acids as interfacial bridges and mineralization induction media, calcium and phosphorus ions cannot achieve site-specific and orderly nucleation. Moreover, after washing, calcium and phosphorus are washed away, forming a finished product mainly composed of hyaluronic acid.
[0089] The rheometer readings showed a storage modulus of 50 Pa and a loss modulus of 20 Pa. This indicates that the product prepared by this method does not exhibit significant structural support.
[0090] like Figure 16 As shown, Figure 16 The image below shows a microscope image of the product prepared in Comparative Example 1. Figure 17 As shown, Figure 17 The rheological properties characterization diagram is for the product prepared in Comparative Example 1.
[0091] Comparative Example 2
[0092] 1. Preparation of pre-formed hydroxyapatite powder: Take 500 mL of deionized water, add 1.0 g of L-serine, and stir at room temperature for 20 min until completely dissolved; then add 4.7 g of calcium nitrate tetrahydrate and 1.58 g of diammonium hydrogen phosphate sequentially, and continue stirring until homogeneous. Adjust the pH of the system to 11 with ammonia water, and react at a constant temperature of 40℃ for 3 h to allow calcium phosphate ions to generate hydroxyapatite material under the induction of amino acids. After the reaction, collect the solid product by centrifugation, and wash it multiple times with anhydrous ethanol and deionized water to remove free amino acids, residual ions and impurities from the surface. After solidification, obtain the hydroxyapatite product. This product does not have a regular spherical structure, but is mainly composed of irregular blocky and flocculent agglomerates. Seal and store for later use.
[0093] 2. Preparation of the aqueous phase: Take 500 mL of deionized water, add 10.0 g of hyaluronic acid (1000 kDa), stir at 28℃ and 400 r / min for 45 min until completely dissolved to form a homogeneous HA aqueous solution. Add 0.3 g of BDDE crosslinking agent, stir for 15 min to disperse evenly, and adjust the pH of the system to 11. Add all the hydroxyapatite product obtained in step 1 to the aqueous phase, and stir continuously at high speed for 30 min to disperse the product in the aqueous phase system as much as possible to obtain a composite aqueous phase.
[0094] 3. Oil phase preparation: 950 mL of medical liquid paraffin + 50.0 g Tween 60, stirred at 28℃ and 600 r / min for 12 min until homogeneous. The above-mentioned complete aqueous phase doped with pre-prepared hydroxyphosphate was added dropwise to the oil phase at a uniform rate and emulsified at a constant temperature for 25 min; then the temperature was raised to 40℃ and reacted at 300 r / min for 3 h. The reaction conditions and post-treatment procedures (precipitation, washing, curing) were completely consistent with those in Example 1.
[0095] Although this comparative example fully retains all components of amino acids, hydroxyapatite, HA, and BDDE, and the process parameters are completely consistent with those of this invention, it lacks the in-situ synchronous nucleation process due to the stepwise process of first pre-preparing hydroxyapatite and then doping and emulsifying it, resulting in a difference from the in-situ bridging composite microspheres of this invention.
[0096] The microspheres exhibit poor morphology and severe agglomeration. The pre-prepared calcium hydroxyphosphate itself is an irregular blocky or flocculent particle, which makes it impossible to disperse evenly in the aqueous phase. Furthermore, during the emulsification process, a large number of secondary agglomerations occur within the aqueous droplets, resulting in mostly deformed particles or agglomerated aggregates that cannot form complete microspheres with uniform particle size and full sphericity.
[0097] Rheometer measurements showed that the storage modulus of the product prepared in this comparative example was significantly lower, at 300 Pa, and the loss modulus was 45 Pa. This indicates insufficient support capacity. Furthermore, the particle size was inconsistent; excessively large particles could easily lead to clumping and swelling after injection.
[0098] like Figure 18 As shown, Figure 18 The image below shows a microscope image of the product prepared in Comparative Example 2. Figure 19 As shown, Figure 19 The rheological properties characterization diagram is for the product prepared in Comparative Example 2.
[0099] Comparative Example 3
[0100] 1. Preparation of hydroxyapatite powder: Take 500 mL of deionized water, add 4.7 g of calcium nitrate tetrahydrate and 1.58 g of diammonium hydrogen phosphate, stir continuously until homogeneous, adjust the pH of the system to 11 with ammonia water, and react at a constant temperature of 40℃ for 3 h with stirring. No amino acids are added to induce the crystal growth of hydroxyapatite. After the reaction, collect the solid by centrifugation, wash repeatedly with anhydrous ethanol and deionized water, and solidify to obtain pure inorganic hydroxyapatite product. This product has no interfacial active groups, and the crystals are severely disordered and aggregated. It is ready for use.
[0101] 2. Construction of HA-amino acid premixed aqueous phase: Take 500 mL of deionized water, add 10.0 g of hyaluronic acid (1000 kDa), stir at 28℃ and 400 r / min for 45 min to dissolve completely; add 1.0 g of L-serine, stir continuously for 25 min to make the amino acid uniformly dispersed and form hydrogen bonds with HA; then add 0.3 g of BDDE and stir evenly, adjust the pH of the system to 11 to obtain the HA-amino acid premixed aqueous phase.
[0102] 3. Incorporation of hydroxyapatite powder into HA-amino acid aqueous phase: All the pure hydroxyapatite inorganic product prepared in step 1 is added into the HA-amino acid premixed aqueous phase and stirred at high speed for 30 min to disperse the powder as much as possible, thus obtaining the composite precursor aqueous phase. At this time, the amino acids are only freely distributed in the HA network and do not participate in the nucleation and growth of hydroxyapatite.
[0103] 4. Emulsification and isothermal crosslinking reaction: 950 mL of medical liquid paraffin and 50.0 g of Tween 60 were stirred at 28°C and 600 r / min for 12 min until homogeneous and transparent. The aqueous phase was then added dropwise at a uniform rate, and the mixture was emulsified at an isothermal temperature for 25 min to form an emulsion system. Subsequently, the temperature was raised to 40°C and the reaction was carried out at 300 r / min for 3 h. The subsequent post-treatment processes, such as precipitation, washing, and curing, were completely consistent with those in Example 1.
[0104] Since amino acids do not participate in the in-situ nucleation and crystal growth of calcium hydroxyphosphate, the final product is fundamentally different from the in-situ bridging composite microspheres of this invention. Due to the lack of in-situ induction and directional regulation by amino acids, the pre-prepared calcium hydroxyphosphate crystals are disordered and highly aggregated; after being emulsified in an aqueous phase, the calcium hydroxyphosphate continues to agglomerate and accumulate secondary within the microspheres, resulting in distorted, unevenly sized, and rough-surfaced particles that lack a regular and rounded micromorphology.
[0105] Rheometer measurements revealed that excessive packing resulted in an excessively high storage modulus of 2500 Pa and a loss modulus of 49 Pa in the prepared product. Furthermore, its irregular structure and excessively large particles meant it was difficult to inject and more likely to rub against tissues, potentially causing inflammation.
[0106] like Figure 20 As shown, Figure 20 The image below shows a microscope image of the product prepared in Comparative Example 3. Figure 21 As shown, Figure 21 The rheological properties characterization diagram is for the product prepared in Comparative Example 3.
[0107] Performance characterization description:
[0108] Microscopic observation revealed that the microspheres prepared in Examples 1-3 had smooth surfaces, were uniformly spherical, and were suitable for injection molding. Comparative Example 1 failed to produce a spherical structure, resulting in a finished product primarily composed of hyaluronic acid. Comparative Example 2 exhibited poor microsphere morphology and severe agglomeration; the pre-prepared calcium hydroxyphosphate itself consisted of irregular, blocky, and flocculent particles, preventing uniform dispersion in the aqueous phase. Comparative Example 3 resulted in a final product with deformed, unevenly sized particles, a rough surface, and lacking a regular, rounded microstructure.
[0109] The rheological properties results showed that Examples 1-3 exhibited good viscoelasticity. However, the product obtained in Comparative Example 1 lacked support, and the product obtained in Comparative Example 2 had a significantly lower storage modulus, indicating insufficient support. The product obtained in Comparative Example 3, due to severe agglomeration, had an abnormally high storage modulus and lacked good injectability.
[0110] Examples 1-3 all exhibited good stability. After 6 months of testing, the residual rate of storage modulus was greater than 90% in all cases.
[0111] Application Example 1
[0112] At room temperature (28°C), 2.5 g of hyaluronic acid was slowly added to 50 mL of sodium hydroxide aqueous solution (1% sodium hydroxide concentration). The solution was stirred at 400 r / min for 30 min to completely dissolve the hyaluronic acid, forming a homogeneous, lumpy, viscous hyaluronic acid aqueous solution. Then, 2.5 g of the organic-inorganic composite hydroxyapatite microsphere powder prepared in Example 1 (dry weight) was added to the above hyaluronic acid aqueous solution. The stirring equipment was adjusted to high-speed stirring mode at 1200 r / min and stirred continuously for 30 min. Due to the high shear force, the agglomerated solid particles were completely dispersed, and the hyaluronic acid polymer chains were fully adsorbed and coated on the surface of the organic-inorganic composite hydroxyapatite microsphere particles, achieving a monodisperse and uniform arrangement of particles in the aqueous phase. Subsequently, 2.0 g of BDDE crosslinking agent was added to the aqueous phase, the system was heated to 40 °C, and the reaction was carried out at a constant temperature of 1200 rpm for 24 h to allow the hyaluronic acid in the aqueous phase to undergo a full crosslinking and curing reaction, forming a dense crosslinked hyaluronic acid coating shell on the surface of the organic-inorganic composite hydroxyapatite microspheres, thus obtaining an aqueous core-shell structured composite particle suspension.
[0113] After the reaction, the mixture was allowed to cool naturally to room temperature and centrifuged at 2000 r / min for 12 min to completely separate the solid-liquid system, collecting the bottom solid composite particles. The particles were washed three times with deionized water to remove adsorbed uncrosslinked hyaluronic acid, free BDDE molecules, and residual ionic impurities. The coarsely washed composite particles were uniformly dispersed in PBS and dialyzed continuously for 48 h, with the PBS replaced every 6 h to thoroughly remove residual small molecule impurities, unreacted crosslinking agents, and free metabolites, ensuring the product's biological purity. After dialysis, the solid particles were collected again by centrifugation and placed in sterile PBS buffer at 37℃ and pH=7.4 for 24 h to obtain fully swollen crosslinked hyaluronic acid-coated organic-inorganic composite hydroxyapatite microspheres. Figure 22 As shown, Figure 22 The image below shows a microscope image of the fully swollen, cross-linked hyaluronic acid-coated organic-inorganic composite hydroxyapatite microspheres prepared in Example 1.
[0114] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing composite hydroxyapatite microspheres, characterized in that, Includes the following steps: An aqueous phase containing hyaluronic acid, 1,4-butanediol diglycidyl ether, hydroxy amino acids, calcium source, and phosphorus source at pH 10-11 was added to an oil phase containing an emulsifier and emulsified at a constant temperature. Then, the temperature was raised to carry out a cross-linking mineralization reaction to obtain composite hydroxyapatite microspheres. The hydroxy amino acid is selected from one or more of L-serine, L-threonine, and L-tyrosine.
2. The preparation method according to claim 1, characterized in that, The volume ratio of the oil phase to the water phase is 1:(0.45~0.55); The mass-volume content of the hyaluronic acid and the water in the aqueous phase is 1%~3%; The mass of 1,4-butanediol diglycidyl ether added is 1% to 5% of the mass of hyaluronic acid; The mass of the added hydroxy amino acid is 5% to 15% of the mass of the hyaluronic acid; The calcium-to-phosphorus molar ratio of the calcium source and the phosphorus source is 1.6 to 1.7; The calcium source has a mass-volume content of 0.9% to 1.0% in the aqueous phase. The phosphorus source has a mass-volume content of 0.3% to 0.4% in the aqueous phase.
3. The preparation method according to claim 1, characterized in that, The molecular weight of the hyaluronic acid is 800 kDa to 1500 kDa; The emulsifier is Tween 60.
4. The preparation method according to claim 1, characterized in that, The temperature for constant temperature emulsification molding is 25℃~30℃; the time for constant temperature emulsification molding is 20 min~30 min.
5. The preparation method according to claim 1, characterized in that, The temperature of the cross-linking mineralization reaction is 35℃~45℃; the time of the cross-linking mineralization reaction is 2 h~4 h.
6. Composite hydroxyapatite microspheres, characterized in that, include: A cross-linked network of 1,4-butanediol diglycidyl ether and hyaluronic acid; Hydroxy amino acids bonded to the cross-linked network; Hydroxyapatite grown in situ on the hydroxy amino acids; The hydroxy amino acid is selected from one or more of L-serine, L-threonine, and L-tyrosine.
7. The composite hydroxyapatite microspheres according to claim 6, characterized in that, The storage modulus of the composite hydroxyapatite microspheres is 900 Pa to 1050 Pa, and the loss modulus of the composite hydroxyapatite microspheres is ≤75 Pa.
8. The composite hydroxyapatite microspheres according to claim 6, characterized in that, The particle size of the composite hydroxyapatite microspheres is 20 μm to 60 μm.
9. A subcutaneous cosmetic filler material, characterized in that, The composite hydroxyapatite microspheres obtained by the preparation method according to any one of claims 1 to 5 or the composite hydroxyapatite microspheres according to any one of claims 6 to 8.
10. The subcutaneous cosmetic filler material according to claim 9, characterized in that, The subcutaneous cosmetic filler material is obtained by suspending the composite hydroxyapatite microspheres in at least one of physiological saline or PBS; Alternatively, the subcutaneous cosmetic filler material is obtained by physically mixing the composite hydroxyapatite microspheres with a medically acceptable carrier; Alternatively, the subcutaneous cosmetic filler material includes the composite hydroxyapatite microspheres and a medically acceptable carrier coated on the composite hydroxyapatite microspheres; The medically acceptable carriers include one or more of cross-linked hyaluronic acid and sodium carboxymethyl cellulose.
Citation Information
Patent Citations
Microsphere for injection filling and preparation method thereof
CN116870248A
Tissue repair filling composite gel as well as preparation method and application thereof
CN121081740A
